Experiences with and perception of patient-reported outcome measurement in patients undergoing knee and hip replacement in Germany - Adriana N. König; Sebastian Himmler; Peter Buschner; Leonie Sundmacher (SpringerOpen, 2023)
Abstract Background Patient-reported outcome measures - PROMs - have been developed to provide an assessment of patients' physical function, symptoms, and health-related quality of life. With patient-centered care becoming increasingly important, several national strategies have been initiated for PROM measurement. However, Germany is only at the beginning of this process. The objective of this study is to assess patients' experience with and perception of completing PROMs in patients undergoing knee and hip replacement in Germany. Methods This study used survey data from patients undergoing hip or knee replacement surgery in a hospital in Germany. Before surgery, patients completed a PROMs survey. After at least 6 months, patients were re-contacted to fill in a questionnaire about their experiences with and perception of the PROMs data collection. Results Most patients either agreed or totally agreed that the time to fill in the questionnaire was appropriate (89%), that the purpose of the PROMs collection was clear (85%), that the questionnaire's content applied to their appointment (73%), and that this systematic assessment was beneficial (81%). The corresponding proportions were 54% for feeling productive while waiting and 50% for feeling that the information in the questionnaire affected the patient-doctor interaction positively. Only few significant associations were found between patient characteristics and the favorability of patients' ratings. There were no significant differences between hip and knee replacement surgery patients regarding the favorability rating on any survey question. Conclusions The results of this study suggest that PROMs collection in the context of hip and knee replacement surgery is practicable and partly also perceived beneficial by patients. Orthopedic procedures could serve as a starting point for broader use and routine PROMs collection in Germany.